Biproducts and Kashina's Examples. Issue 1 (2nd January 2016) - Radford, David E.
Abstract : We revisit a class of examples described in the original article on biproducts, expand the class, and provide a detailed analysis of the coalgebra and algebra structures of many of these examples. Connections with the semisimple Hopf algebras whose dimension is a power of two determined by Kashina are examined. The finite-dimensional nontrivial semisimple cosemisimple Hopf algebras we construct are shown to be lower cosolvable. Some of these have one proper normal Hopf subalgebra and are not lower solvable.